Concerning the choice of viscoelastic solutions in glaucoma shunt surgery - S. A. Volik; A. Kh. Kade; G. A. Chudilova; L. V. Lamtatidze; E. I. Volik (Кубанский научный медицинский вестник, 2015)
Shunt surgery does not have any alternative in refractory glaucoma treatment. The results of this surgical direction are restrained by high risks of intra- and postoperative complications. Considerable fluctuation of intraocular pressure and inflammatory process relate to intraoperative complications. This problem is partly solved by use of viscoelastic fluids nevertheless we do not have precise ideas about qualities of viscoelastic fluids which would be appropriate in this surgery. The comparative study between three groups of viscoelastic fluids in vitro to invextigate the adhesive capacity of leucocytes was carried out. The provocation of adhesive molecules exspression on the leucocytes membranes in experiment was estimated as reaction that activates inflammatory process in the conditions of surgical trauma. Sodium hyaluronate 3% was determined to possess the best qualities. This preparation activate the leucocytes adhesion to a lesser degree, and is capable to be in the anterior chamber for a long time. Use of sodium hyaluronate 3% prevents rough scarring by decreasing inflammation rate.